PENGARUH INFUSA KOMBINASI TEMU IRENG, JAHE, TEMULAWAK, DAN KENCUR TERHADAP KADAR HEMOGLOBIN RATTUS NORVEGICUS ANEMIA - Hidayaturohman Khumaeni, eko; Pipit Miranti, Indira; Nur Cahyani, arinda; Risa Maghfira , Windy; Indira Pipit Miranti (Universitas PGRI Adi Buana Surabaya, 2026)
Anemia is a condition in which the body experiences a decrease in hemoglobin levels below the required normal limits. Black turmeric (temu ireng), ginger, Curcuma (temulawak), and aromatic ginger (kencur) contain compounds with antioxidant and anti-inflammatory activities that can prevent and repair damage caused by oxidative stress, which leads to anemia. Objective This study aims to determine the effect and optimal frequency of administering an infusion combination of black turmeric, ginger, Curcuma, and aromatic ginger on hemoglobin levels in anemic Rattus norvegicus. Methods This study employed an experimental method with a pre-post test control design. Results The four rhizomes used in this study contribute to the treatment of anemia. The isoflavone content in black turmeric and curcumin in Curcuma can prevent hemoglobin damage resulting from oxidative stress caused by sodium nitrite exposure. Other components, such as Ethyl p-methoxycinnamate in aromatic ginger, act as an anti-inflammatory by reducing the production of cytokines IL-1 and TNF-ɑ. Furthermore, the 6-gingerol content in ginger can halt the formation of hepcidin, which inhibits iron absorption, allowing the process of red blood cell formation to continue in the bone marrow. Conclusion: It can be concluded that the infusion combination of black turmeric, ginger, Curcuma, and aromatic ginger can increase hemoglobin levels in anemic Rattus norvegicus. The optimal frequency for increasing hemoglobin levels occurred in the P2 group, with an administration frequency of twice daily. Keywords: infusion, hemoglobin, anemia